2015
DOI: 10.1177/0011000015613142
|View full text |Cite
|
Sign up to set email alerts
|

Helping Skills Training for Undergraduate Students

Abstract: We examined the effectiveness of the Hill model of helping skills training for 191 undergraduate students in six sections of a semester-long course. Students completed self-report, performance, and nonverbal measures at the beginning; they conducted one 20-min helping session at the beginning and another toward the end of the semester; and they completed self-efficacy measures at the end of the semester. Students' helping skills improved over the course of the semester, as evidenced by higher helper-and volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 37 publications
4
64
1
5
Order By: Relevance
“…In addition, ratings of the FIS performance task were also significantly correlated with social skills and the natural helper measure. The magnitude of these correlations was consistent with those reported by Hill et al (), though Anderson, Crowley et al () reported higher magnitude correlates of FIS and social skills. In terms of self‐report measures, a common set of traits were moderately intercorrelated, including prior helping, empathy, social skills, and mindfulness.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, ratings of the FIS performance task were also significantly correlated with social skills and the natural helper measure. The magnitude of these correlations was consistent with those reported by Hill et al (), though Anderson, Crowley et al () reported higher magnitude correlates of FIS and social skills. In terms of self‐report measures, a common set of traits were moderately intercorrelated, including prior helping, empathy, social skills, and mindfulness.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of self‐report measures, a common set of traits were moderately intercorrelated, including prior helping, empathy, social skills, and mindfulness. While FIS was significantly correlated with many of these variables, the overall magnitude of correlations was mild (and similar to patterns reported by Hill et al, ). We were somewhat surprised that participants’ self‐report of their individual FIS was moderately correlated with the expert ratings of the FIS performance.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As its very structured method appeared well suited to a short course, we kept the CMT components (skills, video examples, role plays). We added the theoretical content about the exploration stage from the Hill helping skills model because it had been evaluated as having the best coverage with regard to skills, culture, theory, cognition and affect, and relationship to therapeutic change (Hill et al, 2015 ). In order to remain within the time constraints, our helping skills course was limited to the Exploration level of the psychotherapeutic process (see Hill et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%